Pendugaan kerusakan Akibat Impak pada Buah Apel dengan Metode Elemen Hingga - Yuwana Yuwana (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2003)
Damage caused by impact in apple was predicted using finite element method Apple model was axi-•ymetric three dimensions consisted 779-1 tetrahylrical elemeitts with 1612 nodes representing an apple having 2.5 AlPa Yon; modulus, 0.145 Poisson ratio. 134.5 g mass and 164,4 cm . Impact was simulated by employing an acceleration of 135 g (g = 9,81m/s1) on the model. During simulation, damage was supposed to occur when the stress suffered by cell was greater than its strength. The strength of cell was adopted from the previous study which was 0.44 Zone q